BILINGUALISM AND THE FUTURE OF ARABIC EDUCATION IN THE REPUBLIC OF GHANA/ Ø§Ù„Ø«Ù†Ø§Ø¦ÙŠØ© Ø§Ù„Ù„ØºÙˆÙŠØ© ÙˆÙ…Ø³ØªÙ‚Ø¨Ù„ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø¬Ù…Ù‡ÙˆØ±ÙŠØ© ØºØ§Ù†Ø§ - Muaz, Murtada Mahmoud; Abdullah, Youshau Muhammad (Ijaz Arabi Journal of Arabic Learning, 2019)
Based on two bold recent initiatives by the Ghanaian governments on language policy, this paper investigated the future of Arabic language in Ghana. In 2016, the Government of Ghana declared through the Ministry of Education that Arabic has been made one of the elective subjects at the Senior High and that it might be rendered same at the preparatory level in the near future. At the same time, the government reiterated his determination to make French a second official language in Ghana, in addition to English. It is against this backdrop that this paper shed some insights into the future of Arabic in a bilingual Ghanaian society. It began with a general discussion on the state of Arabic language in Ghana, paving the way for the interrogation of the continuous struggle among powerful nations to impose their language and culture on the developing countries for varied socio-cultural, economic and political interests. In essence, the paper forecasted how Arabic could thrive the competition from the other foreign languages, coupled with the enormous challenges it is already coping with. The article suggests relevant measures that need to be taken by stakeholders to keep Arabic relevant and competitive in Ghana.